Is Mesenteric Ischemia In COVID-19 Patients A Surprise?. (April 2021) - Vartanoglu Aktokmakyan, Talar; Tokocin, Merve; Meric, Serhat; Celebi, Fatih
Aim. The disease caused by the 2019 novel coronavirus is known predominantly for its respiratory outcomes; a subset of critically ill patients demonstrates clinically remarkable hypercoagulability in which thrombotic events range from acute pulmonary embolism in patients with COVID-19 pneumonia to extremity ischemia. Our observational study aimed to describe the incidence and characteristics, as well as clinical outcomes, of patients presenting and treated for mesenteric ischemia during the COVID-19 pandemic. Material and Methods. Between March 13 and May 13, 2020, 60 patients operated for emergency reasons were analyzed, and it was noticed that 5 of the 6 COVID-positive patients were operated due to mesenteric ischemia. Results. Five of sixty patients (83.3%) applied to our emergency clinic with COVID-19 positive and acute abdomen. Two of them (40%) did not have any comorbidities. All of them (%100) were male. There were no complications and only 1 death (20%). Mean leukocyte, neutrophil, and platelet levels were within the normal range, while the lymphocyte level was near the lower limit. C-Reactive Protein was above the limit in all patients. The mean levels of International Normalized Ratio, Platelet, and Activated Partial Thromboplastin Time were above the limits. While D-dimer levels were close to the upper limit; fibrinogen levels were above the normal limit for each patient. Conclusion. The presence of hypercoagulation status in critical COVID-19 patients should be observed closely, and anticoagulation therapy can be considered in selected patients. More clinical data are needed to examine the role of anticoagulation in COVID-19 treatment.